Screening for osteoporosis in Chinese post-menopausal women: a health economic modelling study. Issue 7 (July 2016) - Si, L.; Winzenberg, T.; Chen, M.; Jiang, Q.; Neil, A.; Palmer, A.
Abstract Summary Screening and appropriate treatment for osteoporosis has been proven to be cost-effective in many populations; however, it is not clear in the Chinese population. Simulations using a validated health economics model suggest that screening for osteoporosis in Chinese women is cost-effective and may even be cost-saving in Chinese post-menopausal women. Introduction This study aimed at determining the cost-effectiveness of osteoporosis screening strategies in post-menopausal Chinese women. Methods A validated state-transition microsimulation model with a lifetime horizon was used to evaluate the cost-effectiveness of different screening strategies with treatment of alendronate compared with current osteoporosis management in China. Osteoporosis screening strategies assessed were (1) universal screening with dual-energy X-ray absorptiometry (DXA) alone; (2) Osteoporosis Self-Assessment Tool for Asians (OSTA) + DXA; and (3) quantitative ultrasound (QUS) + DXA with rescreening at 2, 5 or 10-year intervals for patients screened negative by DXA. The study was performed from the Chinese healthcare payer's perspective. All model inputs were retrieved from publically available literature. Uncertainties were addressed by one-way and probabilistic sensitivity analysis. Results Screening strategies all improved clinical outcomes at increased costs, and each were cost-effective compared with no screening in women aged 55 years given the Chinese willingness-to-pay threshold of USD 20, 000 per quality-adjusted life year (QALY) gained. Pre-screening with QUS and subsequent DXA screening if the QUS T-score ≤ −0.5 with a 2-year rescreening interval was the most cost-effective strategy with the highest probability of being cost-effective across all non-dominated strategies. Screening strategies were cost-saving if screenings were initiated from age 65 years. One-way sensitivity analyses indicated that the results were robust. Conclusions Pre-screening with QUS with subsequent DXA screening if the QUS T-score ≤ −0.5 with a 2-year rescreening interval in the Chinese women starting at age 55 is the most cost-effective. In addition, screening and treatment strategies are cost-saving if the screening initiation age is greater than 65 years.